Impaired cellular and humoral immunity is a feature of Diamond‐Blackfan anaemia; experience of 107 unselected cases in the United Kingdom. (13th April 2019) - Iskander, Deena; Roberts, Irene; Rees, Clare; Szydlo, Richard; Alikian, Mary; Neale, Michael; Harrington, Yvonne; Kelleher, Peter; Karadimitris, Anastasios; de la Fuente, Josu
Summary: Diamond‐Blackfan anaemia (DBA) is a rare bone marrow failure syndrome characterised by anaemia, congenital anomalies and cancer predisposition. Although infections are the second leading cause of mortality in non‐transplanted patients, immune function is largely unexplored. We identified quantitative deficits in serum immunoglobulins and/or circulating T, natural killer and B lymphocytes in 59 of 107 unselected patients (55·1%) attending our centre over a 7‐year period. Immune abnormalities were independent of ribosomal protein genotype and arose in both steroid‐treated and steroid‐untreated patients. In summary, these data highlight the high prevalence and spectrum of infections and immune defects in DBA.